If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(-3 + -9m) = -5(11m + -6) (-3 * -10 + -9m * -10) = -5(11m + -6) (30 + 90m) = -5(11m + -6) Reorder the terms: 30 + 90m = -5(-6 + 11m) 30 + 90m = (-6 * -5 + 11m * -5) 30 + 90m = (30 + -55m) Add '-30' to each side of the equation. 30 + -30 + 90m = 30 + -30 + -55m Combine like terms: 30 + -30 = 0 0 + 90m = 30 + -30 + -55m 90m = 30 + -30 + -55m Combine like terms: 30 + -30 = 0 90m = 0 + -55m 90m = -55m Solving 90m = -55m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '55m' to each side of the equation. 90m + 55m = -55m + 55m Combine like terms: 90m + 55m = 145m 145m = -55m + 55m Combine like terms: -55m + 55m = 0 145m = 0 Divide each side by '145'. m = 0 Simplifying m = 0
| 2(2+b)+(2b)=900 | | 5x^2-23z+12=0 | | 4-9=4x | | 5y+9wheny=6 | | 0=15m^2-10m-25 | | 1.10=2x+1 | | 2(y-3)=34 | | 4-8=4x-1 | | y=15m^2-10m-25 | | -12r^2+4=13r | | in(8x)=5.5 | | 3(5-2)=y | | -81-6x=-18+3x | | (5z+6)(3-z)=0 | | -7(x+3)=-16-7a | | 3gh-4h= | | -(3-4m)=7-6m | | 2b-18= | | 8(2(2)+4)-3(3(2)-6)= | | (5x-2)(-5x-4)= | | 3(6-1)=11p-45 | | A^2(b-1)-25(b-1)= | | 2(-5)+7(-25)-9(-5)+21(-50)+5(-5)= | | (k+1)x^2+(k+1)y^2+2kx+2ky+2y+4k+3=0 | | .25x-5+171=x | | 20/12=50/x | | 3(-5)(2)+6(-5)+-5(3(2)-6)= | | 2x+3x+(2+6)=8 | | 7x-2=4x-2 | | y=-2x+16x-24 | | ln(5x-2)-ln(x+3)=2 | | 5(2+p)=17.5 |